The Electrolyte-Fuel Concentrations Effects on Direct Methanol Alkaline Fuel Cell (DMAFC) Through Non-Noble Metal Catalysts - Wika Atro Auriyani; Djoni Bustan; Sri Haryati (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), Institut Teknologi Sumatera, Lampung Selatan, Lampung, Indonesia, 2021)
Most of the R&D on Direct Methanol Alkaline Fuel Cell (DMAFC) concentrates on electrode catalyst and appropriate electrolyte to improve the efficiency. Mostly, a Pt-based electrocatalyst was used. In this research, Nickel foam and membrane silver as non-noble metal catalysts were used in a square-shaped fuel cell stack of 15 x 15 cm in size. The ionic current in the Direct Methanol Alkaline Fuel Cell (DMAFC) was due to the conduction of hydroxide ions. Potassium hydroxide which plays an essential role in delivering hydroxide ions was used in this study. The electrolyte effect of potassium hydroxide was studied in different concentrations for the methanol oxidation reaction. Nickel foam and membrane silver were used for methanol oxidation reaction (MOR) and oxygen reduction reaction (ORR). 1 M, 3 M, 5 M concentration of potassium hydroxide and 0.5 M, 1 M, 2 M, 3 M, 4 M, 5 M of methanol as a fuel have been conducted. The highest maximum power density of 543.35 mW/cm2 was obtained at 2,331 mA/cm2 of current density using the 5 M KOH and 0,5 M fuel. At equimolar concentration between fuel-electrolyte mixture give the higher current density.